Do employees share knowledge when encountering abusive supervision? - Wu, Wei-Li; Lee, Yi-Chih (Journal of managerial psychology, 2016)
Purpose – Despite the prevalence of destructive leadership in today’s workplace, the authors know little about its influence on knowledge sharing among employees. Using the conservation of resources (COR) theory, the authors examine how abusive supervision influences psychological capital and affects knowledge sharing. Further, the authors take a context variable (group trust) to explore its cross-level influence on the above causal relationship. The paper aims to discuss these issues. Design/methodology/approach – This study conducts multi-level analyses of knowledge sharing. Abusive supervision and psychological capital are the determinants of knowledge sharing at the individual level. Group trust is considered a group-level variable with cross-level influences. The final sample for an empirical test conducted using hierarchical linear modeling includes 449 group members of 55 working groups. Findings – Empirical results show that abusive supervision is negatively related to knowledge sharing. The results also indicate that psychological capital mediates the relationship between abusive supervision and knowledge sharing. At the group level, group trust has a direct cross-level impact on employees’ knowledge sharing and mitigates the relationship between abusive supervision and psychological capital. Originality/value – Applying the COR theory, this is the first research to discuss how destructive leadership (i.e. abusive supervision) influences knowledge sharing. Based on the multi-level perspective, the authors also examine how group trust can have a cross-level impact on knowledge sharing and the relationship between abusive supervision and psychological capital.